2000
DOI: 10.1038/labinvest.3780143
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Tsc1 Protein Detected by Immunohistochemistry in Various Normal Rat Tissues and the Renal Carcinomas of Eker Rat: Detection of Limited Colocalization with Tsc1 and Tsc2 Gene Products In Vivo

Abstract: SUMMARY:We and others previously demonstrated that hereditary mutation and a subsequent second hit in the rat homolog of tuberous sclerosis gene (Tsc2) are responsible for Eker renal carcinomas (RC). In humans, alteration in the TSC2 gene is known to cause the tuberous sclerosis complex (TSC) that results in hamartomatous lesions in multiple organs, but the function of TSC2 is not fully understood. In recent years, a second gene (TSC1) responsible for human TSC has been cloned, and binding between TSC1 and TSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 30 publications
2
13
0
Order By: Relevance
“…Like tuberin, hamartin has also been reported to localize to the nucleus (40). If hamartin localizes to the nucleus, a reasonable question would be, do these proteins function within the nucleus as a heterodimer or independently?…”
Section: Discussionmentioning
confidence: 99%
“…Like tuberin, hamartin has also been reported to localize to the nucleus (40). If hamartin localizes to the nucleus, a reasonable question would be, do these proteins function within the nucleus as a heterodimer or independently?…”
Section: Discussionmentioning
confidence: 99%
“…This association has been demonstrated by immunohistochemical colocalization studies (58)(59)(60)(61)(62)(63) as well as by coimmunoprecipitation from subcellular fractions (64). In their elegant series of experiments, Nellist and colleagues (44) showed that hamartin and tuberin are binding partners that coelute from subcellular fractions in a complex with a molecular weight of 450 kD, larger than the combined molecular weights of hamartin and tuberin.…”
Section: Hamartin and Tuberin Physically Interactmentioning
confidence: 99%
“…In rodent organs such as the adrenal, brain, pituitary, small and large intestine, stomach, testis, and retina, the distribution of hamartin and tuberin overlapped, but was not identical, suggesting that hamartin does not always associate with tuberin in all organs and tissues. At the subcellular levels, the two proteins co-localized with each other to some extent, but localization was mostly independent in pancreatic islets, medulla of the kidney, and muscle fibers (24,25). Analysing kidney biology revealed that tuberin and hamartin are specifically expressed in the distal urinary tubule.…”
Section: Discussionmentioning
confidence: 96%